Genome-wide identification of the AcMADS-box family and functional validation of AcMADS32 involved in carotenoid biosynthesis in Actinidia - Lin, Zhiyi; He, Zunzhen; Ye, Daoling; Deng, Honghong; Lin, Lijin; Wang, Jin; Lv, Xiulan; Deng, Qunxian; Luo, Xian; Liang, Dong; Xia, Hui (Frontiers in Plant Science, 2023)
MADS-box is a large transcription factor family in plants, which plays a crucial role in various processes of plant development, however, it has not been systematically analyzed in kiwifruit. In the present study, a total of 74 AcMADS genes were identified in the kiwifruit genome, including 17 Type-I and 57 Type-II members. The AcMADSs were randomly distributed across 25 chromosomes and were predicted to be mostly located in the nucleus. A large number of fragmental duplications were detected in AcMADSs, which might be the main force driving the family expansion. Expression profile analysis showed that AcMADS members had different expression patterns in different tissues and under different stresses. AcMADS32 and AcMADS48 in AG group had high expression levels during fruit development, and AcMADS32 was selected for role analysis in carotenoids synthesis. Stable overexpression of AcMADS32 up-regulated the expression of AcBCH1/2 and increased the zeaxanthin/β-carotene ratio, although the contents of carotenoid components were decreased. The results provide a understanding of the MADS-box gene family in kiwifruit and laid a foundation for further research on their functions during the development of kiwifruit.